Forecasting Model of Gene Enzyme Polymorphism Detoxification in Patients Suffered from HFRS - G. M. Hasanova; A. V. Tutel’jan; D. A. Valishin; A. N. Hasanova (Журнал инфектологии, 2016)
Aim: to study gene enzyme polymorphism of xenobiotic detoxification in patients suffered from HFRS influenced by disease severityProceedings : Molecular genetic checkup has been done in 292 patients suffered from HFRS and 426 seronegative donors.DNA samples isolated from lymphocytes of peripheral gene enzyme were used for molecular genetic checkup. Phenic-chloroform extraction method was applied to isolate DNA. The given DNA was used for polymerase chain reaction of DNA synthesis. Polymorphous CYP1A1 and GSTP1 gene locus analysis was performed on an automatic basis by polymerase chain reaction of DNA synthesis in a thermal cycle «Terzik» produced «DNK–techologiya» ( Moscow city) with the use of locus specific and oligonucleotide primers.Outcomings: Glutathion-S-transferase class π with A313G locus of AG heterozygous genotype is typical for people of Bashkortostan due to underlying risk for HFRS. A combination of genotypes in the form of cytochrome P-450A1 with polymorphous locus A2455G and glutathione-S-transferase class π with A313G locus of AG can be found only in case of severe form of HFRS.